BAS/BSCR13 Increased plasminogen activator inhibitor-1 may explain dexamethasone-induced thrombosis as site of intraluminal wire injury. Issue 17 (26th August 2010) - Low, L; Seckl, J R; Walker, B R; Hadoke, P W F
Abstract : We have previously shown that high-dose glucocorticoid treatment reduces neointimal proliferation following arterial injury in mice, but is associated with increased local thrombosis. Clinically, glucocorticoid excess, either in Cushing's syndrome or with chronic treatment, is associated with increased coagulation and decreased fibrinolysis. The few animal (rat) studies which have investigated these effects support the conclusion that glucocorticoid treatment reduces fibrinolysis. This study aimed to determine the influence of glucocorticoid administration on the thrombotic potential in mice. Male C57Bl/6J mice (aged 10–12 weeks) received either vehicle or dexamethasone (dex; 0.1 or 0.8 mg/kg/day) orally for 5 weeks (n=8/group). Tail tip bleeding time was reduced by high-dose dex (52.9±5.6 s) compared with vehicle (87.1±13.6 s; p<0.05). High-dose dex increased plasminogen activator inhibitor-1 (PAI-1; 139.5±15.1% vs vehicle 100.0±10.7%; p<0.05 and decreased tissue plasminogen activator (tPA; 55.9±4.9% vs vehicle 100.0±10.3%; p<0.05) mRNA levels in the heart. In addition, high-dose dex increased total PAI-1 (3.53±0.59 ng/ml vs vehicle 0.96±0.17 ng/ml; p<0.001) and active PAI-1 (0.92±0.09 ng/ml vs vehicle 0.31±0.07 ng/ml; p<0.001) plasma antigen levels. High-dose dex did not alter platelet activation as measured by p-selectin expression using flow cytometry. Low-dose dex had no effect on any parameters described. Dexamethasone-induced thrombosis at the site of intraluminal wire injury may be attributable to alterations in the endogenous fibrinolytic system rather than changes in platelet activity. These results suggest that beneficial inhibition of neointimal proliferation mediated by systemic glucocorticoid administration is negated in part by changes in fibrinolysis leading to large, semi-occlusive thrombi formation at the site of injury.